Effects of mindfulness meditation combined with progressive muscle relaxation on sleep disorders, anxiety, and depression in patients with sarcopenia undergoing hemodialysis - Wu, Yongyao; Zhang, Haojie; Jiang, Lei; Liu, Zhiping; Li, Xinfei; Guo, Bei; Li, Junyuan; Xu, Pengjie; Liu, Jiang; Yu, Rizhen (Frontiers in Psychiatry, 2025)
ObjectiveLong-term physiological, psychological, economic, and lifestyle pressures make maintenance hemodialysis (MHD) patients prone to anxiety and depression. This study aims to evaluate the effects of mindfulness meditation combined with progressive muscle relaxation on sleep and emotional disorders in hemodialysis patients with sarcopenia.MethodsPatients with uremic sarcopenia and sleep issues were randomly divided into a control group (n=24) and an intervention group (n=25), with an average age of 45.4 ± 4.77 years and an average dialysis duration of 56.86 ± 17.48 months. The control group received standard treatment (hemodialysis three times per week, medication, health education, dietary guidance, and exercise recommendations), while the intervention group additionally underwent home-based mindfulness and relaxation training for at least 0.5 hours daily over 12 weeks. Sleep quality, emotional states, and quality of life were assessed using the Pittsburgh Sleep Quality Index (PSQI), Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale (SAS), and 36-Item Short Form Health Survey (SF-36). Data analysis included descriptive statistics, t-tests, analysis of covariance, Mann-Whitney U tests, and chi-square tests.ResultsBefore the intervention, there were no significant differences between the two groups in sleep, anxiety, depression, or quality of life (P>0.05). After the intervention, the intervention group showed significant improvements in all PSQI dimensions (e.g., sleep medication use, sleep quality, and sleep duration) (P<0.01), significant reductions in SAS and SDS scores (P<0.05), and significantly higher SF-36 scores compared to the control group (P<0.05).ConclusionMindfulness and muscle relaxation training can alleviate psychological stress, reduce skeletal muscle tension, promote muscle anabolism, and significantly improve sleep quality, anxiety, and depression in hemodialysis patients with sarcopenia. This approach is simple, unrestricted, and widely applicable, making it worthy of clinical promotion.LimitationsThe study had a small sample size and a short follow-up period.Clinical trial registrationhttps://register.clinicaltrials.gov/, identifier NCT06261372.